Comprehensive Physiology 2013
DOI: 10.1002/cphy.c110014
|View full text |Cite
|
Sign up to set email alerts
|

Phenomics of Cardiac Chloride Channels

Abstract: Forward genetic studies have identified several chloride (Cl−) channel genes, including CFTR, ClC-2, ClC-3, CLCA, Bestrophin, and Ano1, in the heart. Recent reverse genetic studies using gene targeting and transgenic techniques to delineate the functional role of cardiac Cl− channels have shown that Cl− channels may contribute to cardiac arrhythmogenesis, myocardial hypertrophy and heart failure, and cardioprotection against ischemia reperfusion. The study of physiological or pathophysiological phenotypes of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 169 publications
(273 reference statements)
2
42
0
1
Order By: Relevance
“…[61] Antagonism of such channels may be proarrhythmogenic (via abolished protection against focal triggered arrhythmias) or antiarrhythmic (via prevented reentrant arrhythmias). [6265]…”
Section: Proarrhythmic and Antiarrhythmic Actions Of Sulfonylureasmentioning
confidence: 99%
“…[61] Antagonism of such channels may be proarrhythmogenic (via abolished protection against focal triggered arrhythmias) or antiarrhythmic (via prevented reentrant arrhythmias). [6265]…”
Section: Proarrhythmic and Antiarrhythmic Actions Of Sulfonylureasmentioning
confidence: 99%
“…However, the relationship between ion channels and ROS has not been elucidated in the process of I/R. In particular, anion channels such as chloride ion channel are reported to be involved in the generation of myocardial ischemia reperfusion arrhythmia [6,7]. Early application of anion channel blockers 4,4'-diisothiocyano-2,2'-stilbenedisulfonic acid (DIDS), 4-acetamido-4'-isothiocyanato-stilbene-2,2'-disulphonic acid (SITS) and 5-nitro-2(3-phenylpropylamino) benzoic acid (NPPB) improves the ECG manifestation and reduces the degree of reperfusion arrhythmia [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that CFTR may play a role in maintaining the resting membrane potential and regulating the action potential duration, as well as in minimizing the depolarizing effect of Ca 2+ entry upon β-adrenergic stimulation [8]. An ex vivo study on isolated perfused hearts of CFTR-knockout mice also suggests the involvement of CFTR in mediating ischemic preconditioning [9].…”
Section: Introductionmentioning
confidence: 99%